1987
DOI: 10.1007/bf00915553
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subpopulation profiles and mitogen kinetics in immunological deficiency testing

Abstract: The correlation between lymphocyte proliferative responses to mitogens and T4/T8 ratios was analyzed in a cross section of patients who either were in a high-risk group for HTLV-III infection or fulfilled clinical criteria for acquired immune deficiency syndrome (AIDS). The patient results showed that, correlated with decreased T4/T8 ratios, there was a decrease in mitogen responsiveness first to pokeweed mitogen (PWM), followed by concanavalin A (Con A) and then phytohemagglutinin (PHA). Parallel to this decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…This observation was correlated with the progressive loss of T cells. Radvany et al [6] reported a reduced response to PWM, but not to PHA in a group of patients with a mean T4 cell count similar to that of the patients in our study. Only the patients with a severely diminished T4 cell count showed impaired response, to both mitogens [6].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This observation was correlated with the progressive loss of T cells. Radvany et al [6] reported a reduced response to PWM, but not to PHA in a group of patients with a mean T4 cell count similar to that of the patients in our study. Only the patients with a severely diminished T4 cell count showed impaired response, to both mitogens [6].…”
Section: Discussionsupporting
confidence: 82%
“…Radvany et al [6] reported a reduced response to PWM, but not to PHA in a group of patients with a mean T4 cell count similar to that of the patients in our study. Only the patients with a severely diminished T4 cell count showed impaired response, to both mitogens [6]. The correlation with clinical symptoms showed a decrease of PWM response alone in HIVseropositive individuals, and a decrease of both PWM and PHA in clinically deteriorated HIV-infected patients [16].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This sequential decrease in responsiveness to PWM, Con A, and PHA was also observed by Radvany ei al. [27], but nol by Alcoeer-Varela ci al. [1].…”
Section: Discussionmentioning
confidence: 99%